The Impact of Digital Communication on Customer Loyalty through the Relationship between Brand and Customer, and Customer Citizenship Behavior - Tran, Sy Nguyen (International Review of Management and Marketing, 2025)
Digital communication plays an important role in enhancing customer loyalty. From there, customers are attached to the brand, and are willing to buy and repeat purchasing behavior. The objective of this research examines the impact of digital communication on customer loyalty through customer citizenship behavior, the relationship between brand and customer. Using the survey method, the research collected 324 valid samples for analysis. Research results show that digital communication has a positive influence on relationship between brand and customer, and customer citizenship behavior. The relationship between brand and customer, and customer citizenship behavior have a positive influence on customer loyalty. From there, the research offers managerial implications to enhance customer loyalty.